Molecular Characterization and Expression Analysis of TAK1, TAB1 and TAB2 of Golden Pompano (Trachinotus ovatus) - Yushuai Xie; Kun Lei; Jinquan He; Youchuan Wei (Fishes, 2022)
Transforming growth factor-β (TGF-β)-activated kinase 1 (TAK1), TAK1-binding protein 1 (TAB1) and TAB2 are components of the mitogen-activated protein kinase (MAPK) pathway. In this study, TAK1, TAB1 and TAB2 were characterized from golden pompano (Trachinotus ovatus), a marine fish of great economic value, and named as trTAK1, trTAB1 and trTAB2, respectively. The lengths of the cDNA sequences of the three genes were 2429 bp, 2068 bp and 4229 bp and encoded 575, 506 and 759 amino acids, respectively. The trTAK1, trTAB1 and trTAB2 genes shared high sequence identities and were well clustered with their counterparts from other fish species. Real-time qPCR analysis showed that the three genes were constitutively expressed in all the selected tissues of healthy pompano, and the expression levels of the three genes were significantly up-regulated in head kidney and spleen following Vibrio alginolyticus, lipolysaccharide (LPS) and polyinosinic polycytidylic acid (poly I:C) challenge, indicating their roles in the immune response against pathogens in golden pompano. Our results provide a basis for further study of the functions of these genes in golden pompano.